Hodgkin lymphoma, HIV, and Epstein–Barr virus in Malawi: Longitudinal results from the Kamuzu Central Hospital Lymphoma study. Issue 5 (26th October 2016) - Westmoreland, Katherine D.; Stanley, Christopher C.; Montgomery, Nathan D.; Kaimila, Bongani; Kasonkanji, Edwards; El‐Mallawany, Nader Kim; Wasswa, Peter; Mtete, Idah; Butia, Mercy; Itimu, Salama; Chasela, Mary; Mtunda, Mary; et al.
Abstract: Background: Contemporary descriptions of classical Hodgkin lymphoma (cHL) are lacking from sub‐Saharan Africa where human immunodeficiency virus (HIV) and Epstein–Barr virus (EBV) are prevalent. Methods: We describe a prospective cHL cohort in Malawi enrolled from 2013 to 2015. Patients received standardized treatment and evaluation, including HIV status and EBV testing of tumors and plasma. Results: Among 31 patients with confirmed cHL, the median age was 19 years (range, 2–51 years) and 22 (71%) were male. Sixteen patients (52%) had stage III/IV, 25 (81%) B symptoms, and 16 (52%) performance status impairment. Twenty‐three patients (74%) had symptoms >6 months, and 11 of 29 (38%) had received empiric antituberculosis treatment. Anemia was common with median hemoglobin 8.2 g/dL (range, 3.1‐17.1 g/dL), which improved during treatment. No children and 5 of 15 adults (33%) were HIV+. All HIV+ patients were on antiretroviral therapy for a median 15 months (range, 2–137 months), with median CD4 count 138 cells/μL (range, 23–329 cells/μL) and four (80%) having undetectable HIV. EBV was present in 18 of 24 (75%) tumor specimens, including 14 of 20 (70%) HIV− and 4 of 4 (100%) HIV+. Baseline plasma EBV DNA was detected in 25 of 28 (89%) patients, with median viral load 4.7 (range, 2.0–6.7) log10 copies/mL, and subsequently declined in most patients. At 12 months, overall survival was 75% (95% confidence interval [CI], 55%–88%) and progression‐free survival 65% (95% CI, 42%–81%). Baseline plasma EBV DNA and persistent viremia during treatment were associated with poorer outcomes. Conclusion: cHL in Malawi is characterized by delayed diagnosis and advanced disease. Most cases were EBV associated and one‐third of adults were HIV+. Despite resource limitations, 12‐month outcomes were good.